2002
DOI: 10.1111/j.1756-1051.2002.tb01377.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ontogeny of Swartzia langsdorffii (Leguminosae) pericarp

Abstract: In order to elucidate the position of the Swartzieae in Leguminosae, Swartzia langsdorffii was chosen as a representative of this tribe type genus and subjected to structural studies of immature ovaries (in the floral bud and flowers) and developing and mature fruits. The external epidermis of the ovary is characterized by one layer of thin‐walled polyhedral cells with a thin cuticle. Parenchyma cells have a large quantity of tannin‐containing idioblasts located inside a procambial ring. The one‐layered inner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…De modo geral, a estrutura do ovário e óvulo de Centrolobium tomentosum é similar à observada para outras espécies de leguminosas (Oliveira & Beltrati 1993;Martins & Oliveira 2001;Colpas & Oliveira 2002;Pietrobom & Oliveira 2004;Nakamura & Oliveira 2005;Oliveira & Paiva 2005). Dos dados obtidos, destaca-se o arranjo e composição da superfície ovariana e pericárpica, especialmente os tipos de tricomas e a ocorrência de emergências.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…De modo geral, a estrutura do ovário e óvulo de Centrolobium tomentosum é similar à observada para outras espécies de leguminosas (Oliveira & Beltrati 1993;Martins & Oliveira 2001;Colpas & Oliveira 2002;Pietrobom & Oliveira 2004;Nakamura & Oliveira 2005;Oliveira & Paiva 2005). Dos dados obtidos, destaca-se o arranjo e composição da superfície ovariana e pericárpica, especialmente os tipos de tricomas e a ocorrência de emergências.…”
Section: Discussionunclassified
“…A presença de inúmeros idioblastos fenólicos e sua fusão em canais no pericarpo, também observada no mesocarpo de Swartzia langsdorffii Raddi por Colpas & Oliveira (2002), e o grande acúmulo de compostos fenólicos em toda a epiderme externa da testa são fatos que merecem destaque. Numerosos trabalhos relacionam a ocorrência dos compostos fenólicos à proteção do embrião, especialmente pela resistência que conferem contra patógenos (Suárez & Engleman 1980).…”
Section: Discussionunclassified
“…) and in bracteoles of Mimosa (Leelavathi et al . ); colleters in the bracts of Holocalyx balansae and Zollernia ilicifolia (Mansano & Teixeira ); secretory idioblasts in the perianth of Caesalpinia echinata (Teixeira & Machado ) and in the ovary of Swartzia langsdorffii (Colpas & Oliveira ); and cavities in the perianth of Dahlstedtia (Teixeira & Rocha ; Teixeira et al . ) and in the ovary of Hymenaea stigonocarpa (Paiva & Oliveira ).…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical studies revealed the presence of other types of gland in legume flowers, such as secretory trichomes in Bauhinia (Tucker et al 1984), in the perianth of Indigofera (Kumar et al 1986;Marquiaf avel et al 2009), in the sepals of Dahlstedtia ), in ovaries of Glycine (Healy et al 2009) and in bracteoles of Mimosa (Leelavathi et al 1984); colleters in the bracts of Holocalyx balansae and Zollernia ilicifolia (Mansano & Teixeira 2008); secretory idioblasts in the perianth of Caesalpinia echinata (Teixeira & Machado 2007) and in the ovary of Swartzia langsdorffii (Colpas & Oliveira 2002); and cavities in the perianth of Dahlstedtia (Teixeira & Rocha 2009;) and in the ovary of Hymenaea stigonocarpa (Paiva & Oliveira 2004). However, these secretory structures are not related to the synthesis of floral fragrances in these species, although in other cases, such as Jacaranda oxyphylla (Bignoniaceae) and Phragmopedilum grande (Orchidaceae), floral trichomes secreting volatiles participate in scent production, acting as osmophores (Vogel 1990;Guimarães et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this nature are concentrated on nectaries (Bernadello 2007) and osmophores (Mansano & Teixeira 2008;Marinho et al 2014), secretory structures related to pollination, while other types such as secretory trichomes, idioblasts, cavities and ducts have been less explored in this family comprising such a wealth of species. The few examples available include studies of secretory trichomes in the floral parts of Bauhinia (Tucker 1984, Marinho et al 2016 and Chamaecrista dentata (Meira et al 2014), in the perianth of Indigofera (Kumar et al 1986, Marquiafável et al 2009, in the sepals of Dahlstedtia , in the ovary of Glycine (Healy et al 2009), and in the bracteoles of Mimosa (Leelavathi et al 1984); studies of the colleters in the bracts of Holocalyx balansae and Zollernia ilicifolia (Mansano & Teixeira 2008) and Hymenaea stignocarpa (Paiva & Machado 2006); of the secretory idioblasts in the perianth of Caesalpinia echinata (Teixeira & Machado 2007) and in the ovary of Swartzia langsdorffii (Colpas & Oliveira 2002); and studies of the secretory cavities in the perianth of Dahlstedtia (Teixeira & Rocha 2009, in the ovary of Hymenaea stigonocarpa (Paiva & Oliveira 2004), and of the secretory ducts and cavities in the petals and sepals of Pterodon pubescens, Dipteryx alata and Taralea oppositifolia (Leite et al 2014).…”
Section: Introductionmentioning
confidence: 99%